2014
DOI: 10.1186/1471-2415-14-35
|View full text |Cite
|
Sign up to set email alerts
|

Essential infantile esotropia: postoperative motor outcomes and inferential analysis of strabismus surgery

Abstract: BackgroundThe aim of this retrospective study is a long-term evaluation of postoperative motor outcomes and the inferential analysis of strabismus surgery in infant eyes with essential infantile esotropia.Methods576 patients were compatible with the criteria: confirmed EIE diagnosis, angle ≥ 30 pD, absence of associated ocular anomalies, onset by 6 months of age, absence of hyperopia > 3 Diopters, operation before age 4. Preoperative deviation classes (30–40 pD, 41–59 pD, ≥ 60 pD) were established, different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…3,34 After a long-term evaluation of post-operative motor outcomes in infantile esotropia, Maglia et al suggested a two-horizontal muscle approach in small-angle esotropias and a multiple-muscle surgery in large-angle esotropias. 35 Since many of our patients had large-angle esotropia, three-muscle surgery was frequently done. The choice of surgical technique was also guided by the need to reduce the probability of reoperations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,34 After a long-term evaluation of post-operative motor outcomes in infantile esotropia, Maglia et al suggested a two-horizontal muscle approach in small-angle esotropias and a multiple-muscle surgery in large-angle esotropias. 35 Since many of our patients had large-angle esotropia, three-muscle surgery was frequently done. The choice of surgical technique was also guided by the need to reduce the probability of reoperations.…”
Section: Discussionmentioning
confidence: 99%
“…Rates between 9.9% and 32.4% have been reported by other authors. 13,35,36 Factors such as surgical techniques, pre-operative angle of deviation, duration of follow-up and age at surgery may play a role. In our practice, we do not follow standard surgical tables.…”
Section: Discussionmentioning
confidence: 99%
“…Magli ve ark. 18 yaklaşık 11 yıllık takip sonrasında ±8 pd ortotropya oranını %45 bulmuşlardır. Bu durum postoperatif başarı oranının değerlendirilmesinde ortalama takip süresinin önemini göstermektedir.…”
Section: Discussionunclassified
“…Despite these issues, the outcome was acceptable. Magli et al [15] retrospectively reviewed 576 infantile esotropia patients who underwent surgical treatment and had at least 5 years of follow up. They evaluated results based on the angle of deviation and tried to determine if a specific procedure had a distinct advantage.…”
Section: Standard Surgical Treatmentmentioning
confidence: 99%